Senarai semak kawalan emosi - versi Bahasa Melayu (ERC-M) - Dzulkarnain, Ahmad Aidil Arafat; Jamal, Fatin Nabilah; Musa, Ramli; Jusoh, Masnira; Ahmad Basri, Nadzirah; Shahrudin, Fatin Amira; Sidek, Shahrul Na'im; Md Yusof, Hazlina; Khalid, Madihah (2021)
ERC-M is a parental and teachers report scale to access emotional regulation among school-age children. This questionnaire contains 24 items with two domains (negative liability and emotion liability). The original version of this scale has been validated with high reliability and validity. This scale is the translated and validated ERC in Bahasa Melayu to assess emotional regulation among Malaysian children. Therefore. this scale has high reliability and validity, Therefore, it concludes that it can be used for the population in Malaysia for proper treatment and rehabilitation strategies to help the children in regulating their emotions.